Pengaruh Inflasi, Pemeriksaan Pajak, Peningkatan Ptkp Terhadap Penerimaan Pajak Penghasilan Pasal 21 - Luciana, Ngadiman (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to analyze the effect of inflation, tax audit, and increase in non-taxable income on income tax revenue article 21 for taxpayers at the Kantor Pelayanan Pajak Pratama Jakarta Grogol Petamburan during the 2015-2017 period. This research used a purposive sampling method by taking 29 valid samples from the Kantor Pelayanan Pajak Pratama Jakarta Grogol Petamburan and Badan Pusat Statistik. Data processing techniques using multiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) for Windows verse 24.  The results of this study indicate that increase in non-taxable income  has a significant influence on income tax revenue article 21, while inflation and tax audit have no significant influence on income tax revenue article 21. The implication of this study is the need to increase the role of the government and taxpayers to increase awareness of tax payments that will increase tax revenue article 21.